In-vitro cytotoxicity and antioxidant property evaluation from methanolic extract of Cuscuta Reflexa flowers - Sakib, Md Hossan; Hossain, Mohammad Shahadat; Hossain, Muhammad Sazzad; Mahmood, Asif Al; Sarkar, Md Yasin; Rahman, Sadequr; Shill, Limon Kanti (Asian Journal of Medical and Biological Research, 2015)
This investigation is made upon the plant Cuscuta reflexa, the flowers of it, to find out its Cytotoxicity property. The anti-oxidant property of this plant part was investigated using methanol extraction. Methanolic extract of Cuscuta reflexa.Was used to evaluate its cytotoxicity in Brine shrimp lethality bioassay where vincristine sulphate was used as standard drug. In Brine shrimp lethality bioassay, LC50 value of the extract was 36.72?g/ml and vincristine sulphate served as the positive control showed LC50 value 10.51?g/ml. So, compared to vincristine sulphate, it is evident that the methanol extract of flowers of Cuscuta reflexa was cytotoxic. In case of anti-oxidant the scavenging power (IC50) of DPPH radical was 29.26, 17.07, 18.29, 19.55 and 54.87?g/ml respectively. Asian J. Med. Biol. Res. June 2015, 1(2): 285-291